Implementation of the Uswatun Hasanah Method in Fostering the Moral Action of Students in Islamic Boarding Schools (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
The Uswatun Hasanah method is seen as relevant to strengthen the moral action of students because it emphasizes examples, real actions, and habituation of moral values in daily life, in line with Thomas Lickona's character education framework that integrates moral knowing, moral feeling, and moral action. This study aims to explore the implementation of Uswatun Hasanah in fostering the moral action of students in the context of pesantren, including prioritized moral values, habituation mechanisms, the role of pesantren actors, and the accompanying impacts and constraints. The research uses a qualitative approach with a case study design; The informants consist of kyai/caregivers, asatidz, administrators, and students who are selected purposively and can be equipped with snowballs. Data were collected through semi-structured interviews, observation of routine pesantren activities, and documentation studies, then analyzed thematically through coding and categorization. The findings show that moral values are mapped to morality to Allah, others, and self; Implementation takes place through modeling, habituation of routines, as well as reinforcement and educational correction. The dominant impact was seen in the improvement of discipline, responsibility/trust, social manners, self-control, social concern, and the emergence of moral initiatives; Meanwhile, the main obstacles are related to inconsistencies in example/rule enforcement, peer influence, and limited mentoring.